Implementasi Sistem Informasi Administrasi Presensi Pegawai Berbasis Android - Arera Ayu Anggraeni; Khairullah Khairullah (UNIVED Press, 2022)
Every organization as well as the government really needs a computerized system that is accurate, fast, and efficient. Incompatibility of attendance data can be detrimental to employees, often there is a difference between the attendance listed in the attendance list book/record into the system, which is one of the factors that makes the original data and data that have been verified into a different system. Where using a smartphone GPS system can find out where the location of sub-district employees is, then it is equipped with a direct image capture system so as to reduce employee fraud. how to analyze the development of employee attendance administration information systems using the located based service method. The purpose of this study is to facilitate the attendance of sub-district employees by using the method located based service at the coordinates of attendance.